Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Finally, the JIFAM, Volume 2, Issue Supplement 1, December 2020 can be published, and it consists of 5 papers. This year, the JIFAM is still published bi-annualy in March and September, while this Supplement Issue is an experiment to publish Supplement or Special Issue. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Joural can publish the Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for this second issue of the second volume.